Low-Intensity Exercise Modulates Gut Microbiota to Fight Against Radiation-Induced Gut Toxicity in Mouse Models - Wang, Bin; Jin, Yu-xiao; Dong, Jia-li; Xiao, Hui-wen; Zhang, Shu-qin; Li, Yuan; Chen, Zhi-yuan; Yang, Xiao-dong; Fan, Sai-jun; Cui, Ming (Frontiers in Cell and Developmental Biology, 2021)
Radiation-induced gastrointestinal (GI) tract toxicity halts radiotherapy and degrades the prognosis of cancer patients. Physical activity defined as “any bodily movement produced by skeletal muscle that requires energy expenditure” is a beneficial lifestyle modification for health. Here, we investigate whether walking, a low-intensity form of exercise, could alleviate intestinal radiation injury. Short-term (15 days) walking protected against radiation-induced GI tract toxicity in both male and female mice, as judged by longer colons, denser intestinal villi, more goblet cells, and lower expression of inflammation-related genes in the small intestines. High-throughput sequencing and untargeted metabolomics analysis showed that walking restructured the gut microbiota configuration, such as elevated Akkermansia muciniphila, and reprogramed the gut metabolome of irradiated mice. Deletion of gut flora erased the radioprotection of walking, and the abdomen local irradiated recipients who received fecal microbiome from donors with walking treatment exhibited milder intestinal toxicity. Oral gavage of A. muciniphila mitigated the radiation-induced GI tract injury. Importantly, walking did not change the tumor growth after radiotherapy. Together, our findings provide novel insights into walking and underpin that walking is a safe and effective form to protect against GI syndrome of patients with radiotherapy without financial burden in a preclinical setting.